Epidemiology, pharmacoepidemiology, comparative efficacy and acceptability of drugs in treatment of attention deficit hyperactivity disorder in children and adolescents - Štuhec, Matej (Anali PAZU, 2022)
Attention Deficit Hyperactivity Disorder (ADHD) is commonly diagnosed disorder in children and adolescents. In contrast to North America, where disorder is identified as ADHD, in numerous European countries Hyperkinetic disorder (HKM) is used. The exact cause of ADHD is unknown. The number of diagnosed patients with ADHD is increasing. Epidemiology and pharmacoepidemiology of ADHD in this part of Europe have not been well researched. ADHD treatment guidelines involves pharmacotherapy and non-pharmacological approaches. Effect sizes calculated from meta-analyses should not be the only evidence for clinicians when choosing ADHD medication, but they are a useful tool in choosing pharmacotherapy for ADHD patients.The main aim of this paper is to present the epidemiology and pharmacoepidemiology of ADHD in Slovenia and the comparative efficacy and acceptability of medications for ADHD using meta-analysis.